Early Airway Pathological Changes in Children: New Insights into the Natural History of Wheezing - Bonato, Matteo (J Clin Med, 2019)
Asthma is a heterogeneous condition characterized by reversible airflow limitation, with different phenotypes and clinical expressions. Although it is known that asthma is influenced by age, gender, genetic background, and environmental exposure, the natural history of the disease is still incompletely understood. Our current knowledge of the factors determining the evolution from wheezing in early childhood to persistent asthma later in life originates mainly from epidemiological studies. The underlying pathophysiological mechanisms are still poorly understood. The aim of this review is to converge epidemiological and pathological evidence early in the natural history of asthma to gain insight into the mechanisms of disease and their clinical expression.